Narrativas subversivas no teatro de igreja: dos palcos do Sant’Arte ao protagonismo da minha história - COSTA, Dalila Andréia Cardoso (2024)
Through this academic memorial, I gather some reports and records of my life trajectory linked to my encounter with the Sant'Arte Group, the first space in which I was able to experience art autonomously and collectively. Through these excerpts of narratives I intend to emphasize how the group organized itself among itself to welcome young people, adolescents and adults, from their most diverse origins, beliefs and ways to give life to a space for research and making the theatrical scene, and how our experiences reflected in the dramaturgies and scenic constructions within a Catholic church in Ananindeua, initiating a liturgical-subversive theater. How did this construction take place together with the process of strengthening the identity of the members, most of whom have marginalized experiences (black people, LGBTQIA+ people from the metropolitan and peripheral regions) as subjects in society. I also make a selection of other artistic productions and experiences that are around this long process of selfknowledge by expanding to other spaces such as the School of Theater and Dance of UFPA, such as my participation in shows of the GTU (University Theater Group) as an extension project and my entry into the degree course in theater. This work is also a form of communication for those who, like me, seek to understand the place where they came from, the place in which they are currently inserted and how artistic production in the community can enhance a decolonial pedagogy by seeking references in our own histories.